Efficacy of Aeromonas hydrophila formalin-killed cells and lipopolysaccharides vaccines in maternal immunity of tilapia broodstock and the offspring resistance - Rahma Mulyani; Sukenda Sukenda; Sri Nuryati (Jurnal Akuakultur Indonesia)
ABSTRACT